The politics of administrative data: A case study of school census data for children with SEND - Rempel, Emily; Durrant, Hannah; Barnett, Julie (International Journal of Population Data Science, 2018)
Background From 2016 to 2018 we collaborated on a programme of work with a local authority in the South West of England around understanding diagnosis trends for children with special educational needs and disabilities (SEND). Tracking SEND is a key issue for both local and national government due to the high cost of provision and perceived increases in diagnoses prior to 2010. Objective In this presentation we explore the use of school census data for research and commissioning in local government. Methods We supplement statistical reports of SEND diagnoses from 2011 to 2017 with semi-structured interviews with individuals who inform their decision making with these and similar data. We draw on theories of narrative and causal story-telling to understand how modern statistical analysis is used as a tool to develop commissioning decisions. This includes testing narratives using data as well as data being used to inform narratives. Early Findings and Conclusions We add to a growing area of literature that discusses data and statistics as subjective policy tools. Early results include the use of data as a perceived objective tool in calming emotions during commissioning negotiations. We aim to describe how these decisions are made and what this means for service provision for children with SEND.